Diastereoselective Synthesis of Spiro[benzopyrrolothiazole-thioazlactone] Derivatives from Erlenmeyer Thioazlactones and Azomethine Ylides - Yavari, Issa; Shirazi, Hamideh; Sheikhi, Sara; Taheri, Zohreh (Synthesis, 2022)
Erlenmeyer thioazlactones reacted with 3-(2-oxo-2-arylethyl)benzo[d]thiazol-3-ium bromides in the presence of Et3N in MeCN to afford 1-aryloyl-2′-(benzylthio)-2-aryl-2,3a-dihydro-1H,5′H-spiro[benzo[d]pyrrolo[2,1-b]thiazole-3,4′-thiazol]-5′-ones. Formally, this transformation can be regarded as a Huisgen reaction of the exocyclic carbon–carbon double bond of the Erlenmeyer thioazlactones and azomethine ylides generated in situ. Evidence for the structure of a product was obtained from single-crystal X-ray analyses. The important feature of this reaction is the fact it forms four stereogenic centers, one of which is quaternary, with excellent selectivity.
Keywords: azomethine ylides; conjugated rings; Huisgen reaction; spiro compounds; Erlenmeyer thioazlactones